Cashless Policy and The Nigerian Rural Economy (a Case Study Of Akwa Ibom State) - Udoinyang, Nathan; Daniel , Reuben; Umoh, Salamat Amos Umoh (International Journal of Economic, Finance and Business Statistics, 2024)
This study examines the impact of cashless policy on the Nigerian rural economy, using Akwa Ibom State as a case study. A survey of 328 people from three senatorial districts was conducted, with a sample size of 400. The study found that cashless policy helps in tracking expenses, preventing cash flow outside the formal banking system, reducing money laundering, and reducing stress during payments. However, challenges such as inadequate payment channels, internet fraud exposure, poor electronic banking networks, and high charges hinder its implementation. The researchers urge the government and policymakers to provide reliable methods to combat internet fraud, reduce charges on electronic banking platforms, and educate the public on the benefits of cashless policies.